Effects of Sacharomyces cereviceae Incorporated Diet on Growth Performance, Apparent Digestibility Coefficient of Protein and Survival Rate of Catfish (Pangasius hypothalamus) - rachmawati, diana; Samidjan, Istiyanto; Nugroho, Ristiawan Agung; Susilowati, Titik (Aquacultura Indonesiana, 2019)
One of the solutions to maximize diet usage when the feeding is not in line with the growth of Catfish (Pangasius hypothalamus) is by introduction of fish new culture system.  The new culture system is by incorporating Saccharomyces cerevisiae into the feed.  It aims to increase feed efficiency; in turn it increases the growth.  The objective of the research is to study the effects of S.cereviceae incorporated diet on growth performance, apparent digestibility coefficient of protein and survival rate of catfish (P. hypothalamus).  The fish used in the study were 4.02±0.22 g per fish. The study used experimental method with completely random Design.  The experiments were in 4 (four) treatments.  Each treatment had 4 (four) repetitions.  The treatments were by feeding fish with 4 (four) different dosages of S. cerevisiae addition in the diet.  The dosages were 0 g per kg feed (A), 0.5 g per kg feed (B), 1 g per kg feed (C) and 2 g per kg feed (D).  The results show that the incorporated S. cerevisiae feed was significant (P<0.05) on the specific growth rate (SGR), apparent digestibility coefficient of protein (ADCP) and survival rate (SR) of the catfish (P. hypothalamus) fingerlings.  The best dosage was 1.0 g of S. cerevisiae per kg feed and the optimum dosage ranged from 1 to 1.12 g/kg feed for SGR, ADCP and SR of the Catfish (P. hypothalamus) fingerlings.